2018
DOI: 10.1177/1099800418774633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Positive Pressure Treatment of the Airway on Health-Related Quality of Life in Elderly Patients With Obstructive Sleep Apnea

Abstract: Therapy with CPAP in elderly patients with OSA helps improve their HRQL and reduces daytime sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
2
0
3
Order By: Relevance
“…Of all the possible therapeutic modalities, continuous positive airway pressure (CPAP) therapy still remains the gold standard in OSAS therapy 7 . CPAP therapy leads to an improvement in quality of life 8 , and may reduce certain health risks if the adherence of the patient is sufficient 9,10 . Sufficient adherence is defined by most studies as the use of CPAP for over 4 hours per night on average, however it is unclear if such adherence is enough to achieve the full extent of the possible benefits of the therapy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Of all the possible therapeutic modalities, continuous positive airway pressure (CPAP) therapy still remains the gold standard in OSAS therapy 7 . CPAP therapy leads to an improvement in quality of life 8 , and may reduce certain health risks if the adherence of the patient is sufficient 9,10 . Sufficient adherence is defined by most studies as the use of CPAP for over 4 hours per night on average, however it is unclear if such adherence is enough to achieve the full extent of the possible benefits of the therapy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Algunos investigadores afirman encontrar relación entre apnea obstructiva del sueño y calidad de vida de las personas de edad avanzada [5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Resultados Sobre La Relación Apnea Obstructiva Del Sueño Y Calidad De Vida En Personas De Edad Avanzadaunclassified
“…La apnea obstructiva del sueño produce, en personas ancianas, según la mayoría de los estudios revisados [5][6][7][8][9][10][11][12][13][14][15] , un deterioro de la calidad de vida, aunque existe disparidad en los resultados, ya que ciertas investigaciones 17,18 afirman que a partir de cierta edad (70 años aproximadamente) se produce una estabilización en la calidad de vida de las personas que padecen apnea del sueño.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A recent meta-analysis of data for 63,647 participants concluded that OSAS was an independent risk factor for DM after adjustment for age, sex, and body mass index (BMI) [13]. These observations are not surprising as OSAS and DM share the same risk factors, namely obesity and aging [14]. The high prevalence of OSAS in the DM population, between 23 and 48%, confirms this strong association [15].…”
Section: Introductionmentioning
confidence: 99%